FROM STANDARDIZATION TO FLEXIBILITY: LITERATURE REVIEW ON THE TRANSITION FROM THE 2013 CURRICULUM TO THE MERDEKA CURRICULUM - Ulin Naini; Hasdiana (International Journal of Teaching and Learning, 2025)
Purpose. This study aims to analyze the transition from the 2013 Curriculum (K-13) to the Merdeka Curriculum in Indonesia by examining the shift from standardization to flexibility. It addresses the need to understand the rationale, implementation challenges, and opportunities of curriculum reform during the transition period toward a unified national curriculum. Method. The study employs a qualitative literature review approach. Data were collected through a systematic search of Scopus-indexed journal articles, policy reports, and academic proceedings published between 2013 and 2025. Thematic content analysis was applied to identify key patterns in curriculum design, teaching strategies, assessment systems, and governance of implementation. Findings. The review reveals that K-13 emphasized standardized competencies and authentic assessments but was often perceived as rigid and administratively burdensome for teachers. Conversely, the Merdeka Curriculum highlights flexibility, teacher autonomy, project-based learning (Projek Penguatan Profil Pelajar Pancasila/P5), and formative assessment practices. While this shift aligns with 21st-century learning demands, challenges remain in terms of teacher readiness, infrastructure gaps, and unequal institutional support across regions. Implications. The study underscores that the success of the Merdeka Curriculum is strongly dependent on teacher quality, school leadership, and sustained policy support. It recommends capacity-building programs for educators, structured monitoring mechanisms, and longitudinal evaluations to ensure equitable and effective implementation. This research contributes to the broader discourse on curriculum reform in developing countries by providing a comprehensive synthesis of Indonesia’s experience.